Atmospheric and oceanic patterns influence on midto-late Holocene climate from Pico Island (Azores archipelago) - Hernández, A.; Raposeiro, P. M.; Sáez, Alberto; Gonçalves, Vítor; Bao, Roberto; Pueyo Mur, Juan José; Trigo, Ricardo M.; Giralt, Santiago (2018)
European climate is partly conditioned by a number of atmospheric and oceanic patterns which occur in the North Atlantic sector. The favourable location of the Azores Archipelago (37°–40°N, 25°–31°W) results in a privileged setting to generate high-resolution Holocene climatic proxy data that can contribute to deep our understanding on the evolution of these atmospheric and oceanic patterns. Here, we present a new high-resolution climate reconstruction based on the Caveiro Lake sedimentary sequence in order to fill this gap. Previously, Björck et al. (2006) studied a section of this sequence (the uppermost 4.6 m; 6 Ka cal BP) concluding arid periods occurred during decreased North Atlantic SST and evaporation linked to disturbances in the thermohaline circulation as a consequence of increased drift-ice in the North Atlantic. In turn, the NAO impact was the main atmospheric driver of short-term precipitation changes. The new studied sequence (9.55 m long, 8.2 Ka cal BP) has been analysed at decadal-to centennial timescale resolution for X-ray diffraction, X-ray fluorescence core scanning and elemental and isotope geochemistry on bulk organic matter. The comparison of the Aridity index of Björck et al. (2006) with the new climate reconstruction carried out in this work for the last 6000 years clearly shows that the arid phases of the index fit with the instantaneous sedimentation events defined by both tephra layers and external loadings deposited into the lake. Therefore, these arid events were not triggered by North Atlantic drift-ice variations but by volcanic eruptions and extraordinary rainfall events. Nevertheless, preliminary data of this study suggest that the decadal to centennial evolution of the Caveiro Lake was dominated by the NAO and the North Atlantic SSTs variations. This research is funded through the PaleoNAO (CGL2010-15767), RapidNAO (CGL2013-40608-R) and PaleoModes (CGL2016-75281-C2) Spanish projects. Peer Reviewed